La miocapsulotomía endoscópica (MC) como tratamiento de la hiperplasia benigna de próstata. - Corral Rosillo, J.; Chicharro Almarza, J.; Hernández Villaverde, A.; Luengo Alpuente, S.; Mohamed Mohamed-abdallah, Z.; Moreno Sierra, Jesús; Resel, Luis; Gómez Vegas, Ángel; Silmi Moyano, A.; Blázquez Izquierdo, J. (Clínicas Urológicas de la Complutense, 1993)
Sin resumen